Big data analytics for supporting managerial decision-making in the digital economy - Seidykh, Olga (My University, 2025)
Big data serves as a strategic foundation for building intelligent, adaptive, and innovative organizations capable of thriving in a rapidly changing digital economy. Великі дані слугують стратегічною основою для побудови інтелектуальних, адаптивних та інноваційних організацій, здатних процвітати в умовах швидкозмінної цифрової економіки.
Keywords: big data; decision making; кафедра інформаційних технологій, штучного інтелекту і кібербезпеки; стратегічне управління підприємством; великі дані